Job Offer Negotiations: A Focused Research Approach - Chapman, Elizabeth; Corner, A.J.; Miles, Edward (Université d'Ottawa | University of Ottawa, 2017)
Researchers and employers are typically united in their beliefs that human capital is critical to organizational success and that effective hiring is vitally important. Acquiring and keeping talented employees often requires engaging in negotiation of compensation and of terms of job offers. However, the academic negotiation literature has focused very little on compensation and job offer negotiations. In an attempt to provide guidance for such empirical research, we (a) summarize what is currently known through empirical evidence about job offer and compensation negotiations, and (b) present a research strategy to guide empirical investigations of compensation and job offer negotiations.
Keywords: Job offer negotiation; Compensation negotiation